Physico-microbial and shelf life analysis of commercially important three mango varieties under different treatments (Journal of the Bangladesh Agricultural University, 2020)
Every year huge quantity of mangoes is lost due to lack of proper postharvest storage condition. Various treatments are used to minimize postharvest losses and extend shelf life. So, an experiment was carried out at the Laboratories of the Department of Horticulture and Department of Biochemistry and Molecular Biology, Bangladesh Agricultural University, Mymensingh during the period from July to October, 2018 to investigate the effect of variety and different postharvest treatments to extend shelf life of mango. The two-factor experiment was laid out in Randomized Complete Block design with three replications. The factors taken for the experiments were (i) three varieties of mango, viz., V1= Langra, V2= Fazli and V3= Ashwina and (ii) six postharvest treatments, viz., T1 = control; T2 = perforated low density polythene (LDPE) bag with KMnO4 ; T3 = perforated LDPE bag without KMnO4 ; T4 = mustard oil coating; T5 = hot water treatment (50º C) for 5 minutes; T6 = garlic extracts. Freshly harvested mango was treated with those different treatments. Untreated mango was considered as control. The treated fruits showed significant differences in case of peel color, firmness, total weight loss, disease incidence and severity, and shelf life compared to control fruits. Among the treatments, T2 perforated LDPE with KMnO4 showed the longest shelf life (12 days), less disease incidence and severity and the lowest weight loss at 9 DAS days after storage. The treatment T5 (hot water treatment @ 50º C for 5 minutes) was also found effective for maintaining postharvest quality of mango stored at ambient conditions.J Bangladesh Agril Univ 18(1): 40–46, 2020https://doi.org/10.5455/JBAU.94734